Positive emotion enhances conflict processing in preschoolers. Issue 5 (9th December 2021) - Berger, Philipp; Grosse Wiesmann, Charlotte
Abstract: The rapid detection and resolution of conflict between opposing action tendencies is crucial for our ability to engage in goal‐directed behavior. Research in adults suggests that emotions can serve as a "relevance detector" that alarms attentional and sensory systems, thereby leading to more efficient conflict processing. In contrast, previous research in children has almost exclusively stressed the impeding influence of emotion on the attentional system, as suggested by the protracted development of performance in "hot" executive function tasks. Do preschool children show a facilitative effect of emotion on conflict processing? We addressed this question applying a modified version of a color flanker task that either involved or did not involve positive emotional stimuli in preschool children ( N  = 43, with preregistered Bayesian sequential design, aged 2.8–7.0 years). Our results show a robust conflict effect with higher error rates in incongruent compared to congruent trials. Crucially, conflict resolution was faster in emotional compared to neutral conditions. Furthermore, while efficient conflict processing increases with age, we find evidence against an age‐related change in the influence of positive emotion on conflict processing. Taken together, these findings provide indication that positive emotion can trigger efficient control processes already from early on in life. In contrast to the predominant view in developmental psychology, this indicates that, depending on the role that emotion has in conflict processing, emotion may show a facilitative or impeding effect already in the preschool period.